2022
DOI: 10.1002/joa3.12741
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of thehERGK+channel for the management of the longQTsyndrome: A review

Abstract: In the human heart, the rapid delayed rectifier K+ current (IKr) contributes significantly to ventricular action potential (AP) repolarization and to set the duration of the QT interval of the surface electrocardiogram (ECG). The pore‐forming (α) subunit of the IKr channel is encoded by KCNH2 or human ether‐à‐go‐go‐related gene 1 (hERG1). Impairment of hERG function through either gene mutation (congenital) or pharmacological blockade by diverse drugs in clinical use (acquired) can cause a prolongation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 86 publications
(378 reference statements)
0
6
0
Order By: Relevance
“…None of the stereoisomers increased the threshold of ac‐arrhythmia, with the intrinsic activities being at the most 11%: such a mild effect was observed that the EC 50 values were not determined. Looking at the flip side, being known that hERG agonists are associated with a substantial risk of proarrhythmia, [ 13,46,47 ] no arrhythmogenic effect was observed, this result highlighting the inability of our compounds to alter cardiac rhythm as a side effect.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…None of the stereoisomers increased the threshold of ac‐arrhythmia, with the intrinsic activities being at the most 11%: such a mild effect was observed that the EC 50 values were not determined. Looking at the flip side, being known that hERG agonists are associated with a substantial risk of proarrhythmia, [ 13,46,47 ] no arrhythmogenic effect was observed, this result highlighting the inability of our compounds to alter cardiac rhythm as a side effect.…”
Section: Resultsmentioning
confidence: 93%
“…Notably, both the tested stereoisomers proved to have mixed mechanisms by combining properties of the different types of the hERG potassium channel activators. Considering that Type 2 activators have been reported as drugs with a risk of repolarization overcorrection that could itself be pro‐arrhythmic, [ 46,47 ] unlike Type 1 activators, [ 48,49 ] the observed mixed mechanism suggests a safer cardiac profile for the most potent RS isomer compared with both the previously reported RR enantiomer and the other Type 2 activators reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…While high-throughput virtual screening has primarily focused on the evaluation of a substantial number of drug-induced arrhythmic compounds, it has also unexpectedly revealed agonists (activators) that can induce inward rectification of I Kr (24). The intricate mechanistic properties of each of these compounds show distinct differences, including delayed deactivation, inhibition of C-type inactivation, increased channel open probability, or a combination of these effects, while also indicating unique binding interactions between each activator and the channel (25). Several activators have been studied as potential candidates for different congenital LQTS mutations (25).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the behavior of these activators may vary between different mutants. Nevertheless, most activators primarily target the C-type inactivation mechanism and represent a novel approach to the prevention of ventricular arrhythmias associated with LQTS (25). One such compound is ICA-105574, a derivative of 3-nitro-n-(4-phenoxyphenyl) benzamide and is the most potent I Kr activator to date (26, 27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation